PENGEMBANGAN SMART VILLAGE MELALUI PROGRAM PEMASANGAN WIFI DI DESA SUMBER MEKAR MUKTI KECAMATAN TANJUNG LAGO KABUPATEN BANYUASIN - Ningsih, Erna Widiyati; Febriyanti, Doris; Amaliatulwalidain, Amaliatulwalidain (ITB AAS Indonesia Surakarta, 2024)
The development of the Smart Village in Sumber Mekar Mukti Village was carried out top-down through the signing of a memorandum of understanding (MoU) from CSR, namely PT. Telkom Indonesia, Tbk. In 2022. This research aims to find out the extent of the implementation of the Smar Village dimensions in Sumber Mekar Mukti Village as well as the factors inhibiting the implementation of the Wifi installation program. The theory used is Ramachandra's Theory (2015), which refers to Herdiana's (2019) study, namely the Smart Government, Smart Community and Smart Environment indicators. This research was conducted using qualitative research methods, with a phenomenological case study approach. Data collection techniques are carried out through observation, interviews and documentation. The results of this research show that the implementation of Smart Government, Smart Community and Smart Environment in Sumber Mekar Mukti Village is not yet in accordance with what was expected, in the Smart Government indicator itself the implementation of public and social services is still not optimal because there are still many people who come directly to village office. In the Smart Community indicator itself, community participation in contributing and making decisions is not yet optimal, because there are still people in Sumber Mekar Mukti Village who do not understand government policies, and digital technology users are limited to information only on the WhatsApp feature. Community participation in this case related to the Smart People dimension is also the main key in sustainability indicators. Community participation as the subject of program implementation plays an important role in the development of Smart Villages in villages. The Smart Environment indicator here is not yet running according to the existing concept, because many people still do not know about public information and have not received public services from the Sumber Mekar Mukti Village government, this is due to a lack of socialization and the absence of a SID Website to make it easier for the people of Sumber Mekar Mukti Village. Blooming Mukti. The inhibiting factors in implementing Smart Village development in Sumber Mekar Mukti Village are the community's limitations in accessing ICT for the elderly and limited facilities and infrastructure related to smartphone (cellphone) ownership for accessing information in the village.